(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2022)
This paper aims to shed light on the process and echoes of the allegorical vision developed by Alejandra Pizarnik throughout her poetry. Understanding allegory as a rhetorical resource with enormous imaginative potential, it became a conceptual and aesthetic language capable of translating and communicating abstract ideas and images generated by a single focus which, according to our observation, is represented in the element of the “wind”. Associated with the poet’s intention to keep the past in its most abstract aspect, the analysis of her allegorical process will be concentrated on its intangible, oneiric or even spiritual dimension that transforms allegory in a technique to poetize the past. Likewise, we will define thematically the feelings evoked by the past recovered allegorically by the poet.